The Oral Literaty of Rejung Rasan-Dirasan in Musi Rawas Regency: Form Analysis of Garap - Halilintar, Mark Dhaksa; Ibnan Syarif, Muh.; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2021)
This study aims to describe the form of garap on music accompaniment of Rejung Rasan-Dirasan in Musi Rawas Regency. This study used the descriptive qualitative method. The data collection used: (1) recording technique, both audio and audiovisual; (2) notes; (3) in-depth interviews with some informants; (4) literature study and documentation analysis. The primary data source analyzed was Cikwan as the speaker and some of the public figures in Musi Rawas Regency, South Sumatra. The study results show that the garap form of oral-literary is different from the music structure of Javanese gamelan tradition in general. It submits to the techniques of Rejung Rasan-Dirasan in Musi Rawas Regency. ——- This study aims to describe the form of working on the musical accompaniment of Rejung Rasan-Drasan in Musi Rawas Regency. This study used descriptive qualitative method. Data collection techniques in this study used: (1) recording techniques, both audio and audiovisual, (2) recording, (3) in-depth interviews, (4) literature study and documentation analysis. The main data sources analyzed were Cikwan as a speaker and several community leaders in Musi Rawas Regency, South Sumatra. The results of this study indicate that the form of working on the oral literary art of Rejung Rasan-Dirasan is out of the structure of the rules of Javanese gamelan music which is certainly different from the structure of Javanese music in general but is subject to the technique in the musical Rejung Rasan-Drasan in Musi Rawas Regency.